2006
DOI: 10.4141/a05-090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding level and dietary oil supplementation on apparent ileal and total tract digestibilities of phosphorus and calcium in pigs fed low-phosphorus diets supplemented with microbial or wheat phytase

Abstract: Steiner, T., Mosenthin, R. and Greiner, R. 2006. Influence of feeding level and dietary oil supplementation on apparent ileal and total tract digestibilities of phosphorus and calcium in pigs fed low-phosphorus diets supplemented with microbial or wheat phytase. Can. J. Anim. Sci. 86: [479][480][481][482][483][484][485][486][487][488]. Two experiments were conducted with pigs fitted with simple T-cannulas at the distal ileum to evaluate the effect of energy (ME) intake implemented by variation of feeding level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…However, the values for ATTD of acid hydrolyzed ether extract and ether extract were almost identical, further indicating that complexes between Ca and fat were not excreted in the feces. These results are also in agreement with observations indicating that there is no influence on the digestibility of Ca by addition of fat to conventional diets fed to pigs (Steiner et al, 2006;González-Vega et al, 2015). However, data from humans have indicated that increasing the concentrations of dietary Ca may result in formation of insoluble complexes between Ca and fat, leading to excretion of Ca and fat in the feces, which may result in weight loss (Davies et al, 2000;Zemel et al, 2000;2002;Zemel, 2001;Heaney, 2003;Lorenzen et al, 2007;Bendsen et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the values for ATTD of acid hydrolyzed ether extract and ether extract were almost identical, further indicating that complexes between Ca and fat were not excreted in the feces. These results are also in agreement with observations indicating that there is no influence on the digestibility of Ca by addition of fat to conventional diets fed to pigs (Steiner et al, 2006;González-Vega et al, 2015). However, data from humans have indicated that increasing the concentrations of dietary Ca may result in formation of insoluble complexes between Ca and fat, leading to excretion of Ca and fat in the feces, which may result in weight loss (Davies et al, 2000;Zemel et al, 2000;2002;Zemel, 2001;Heaney, 2003;Lorenzen et al, 2007;Bendsen et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Supplementation of soybean oil to diets fed to pigs does not influence the digestibility of Ca and P (Steiner et al, 2006;González-Vega et al, 2015). In contrast, in humans, increasing dietary Ca intake reduces the digestibility of fat (Bendsen et al, 2008), and elevated levels of dietary Ca and vitamin D may increase the loss of energy by fecal excretion of indigestible com-plexes between Ca and fat (Soares et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The observation that the ATTD of Ca and P is not affected by the level of feed intake agrees with results for growing pigs indicating that the ATTD of Ca and P was not different between pigs fed 2.3 and pigs fed 2.8 times the requirement for maintenance (Mroz et al 1994). However, an increase in the ATTD of P as the level of feed intake by growing pigs increased has also been reported (Steiner et al 2006). It is not clear why level of feed intake appears to have no effect on the ATTD of Ca and P in sows, but it is possible that the different requirements between sows and growing pigs and the differences in stored Ca and P in the body between the two groups of animals are responsible for these differences.…”
supporting
confidence: 87%